2020
DOI: 10.1177/1558925020948219
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the factors affecting the dimensional stability of socks using full-factorial experimental design method

Abstract: Socks, which are a necessary item of clothing, need to be comfortable, affordable, and retain their quality throughout their life. Dimensional stability is one of the basic requirements of socks. The purpose of this study is to investigate the contributing factors, that is, elastane percentage, main yarn material, and process type on dimensional stability of socks. Four different percentages of elastane in plaiting yarn (4%, 6%, 8%, and 10%), two main yarns materials (100% cotton and polyester/cotton 52/48), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Many scientific papers have analyzed the improvement of the properties of socks using different types of fibers, e.g., cotton, wool, acrylic or their blends, and either blended or not with polyester, polyamide and/or elastane [ 1 , 5 , 10 , 11 , 12 , 13 , 14 , 15 ]. Few authors include viscose and bamboo, soybean, flax [ 16 , 17 , 18 , 19 ] and even reclaimed the cotton fibers [ 20 , 21 ] in the analysis of the sock knits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many scientific papers have analyzed the improvement of the properties of socks using different types of fibers, e.g., cotton, wool, acrylic or their blends, and either blended or not with polyester, polyamide and/or elastane [ 1 , 5 , 10 , 11 , 12 , 13 , 14 , 15 ]. Few authors include viscose and bamboo, soybean, flax [ 16 , 17 , 18 , 19 ] and even reclaimed the cotton fibers [ 20 , 21 ] in the analysis of the sock knits.…”
Section: Introductionmentioning
confidence: 99%
“…Dimensional stability is one of the basic requirements for socks [ 11 ]. The leg and sole parts can undergo major shrinkage after washing, which affects the usability of the socks due to size mismatching problems [ 5 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fabrics made from hydrophobic fi bers shrink less or do not shrink during the washing process. The results from studies have shown that with the increasing of the elastane or polyester percentage, the fabric shrinkage is decreasing [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…2 As shown in experiments and field research, after such treatments as hydrothermal processing and bleaching, as well as functionalization sock products tend to change their dimensional stability leading to changes in dimensional and comfort properties, that must be considered when designing a new product and its technology. 3 Thread pre-treatment before knitting/weaving is important as part of the anticipated integration of the wearable electronic components -sensors, electro conductive threads, capacitors into the modified textile products, such as socks, T-shirts, sweaters. 4 In most cases it is appropriate to insert a functional coating on the finished product during the final finishing process.…”
Section: Introductionmentioning
confidence: 99%
“…2 As shown in experiments and field research, after such treatments as hydrothermal processing and bleaching, as well as functionalization sock products tend to change their dimensional stability leading to changes in dimensional and comfort properties, that must be considered when designing a new product and its technology. 3…”
Section: Introductionmentioning
confidence: 99%